Quantitative analysis of catecholamines and their metabolites in human urine by gas chromatography - mass spectrometry as a screening method for sympatho-adrenal tumors - Ubbink, Johan B. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.